Antibacterial Activity of Endophytic Bacteria Against Sugar Beet Root Rot Agent by Volatile Organic Compound Production and Induction of Systemic Resistance - Safara, Somayeh; Harighi, Behrouz; Bahramnejad, Bahman; Ahmadi, Slahadin (Frontiers in Microbiology, 2022)
The volatile organic compounds (VOCs) produced by endophytic bacteria have a significant role in the control of phytopathogens. In this research, the VOCs produced by the endophytic bacteria Streptomyces sp. B86, Pantoea sp. Dez632, Pseudomonas sp. Bt851, and Stenotrophomonas sp. Sh622 isolated from healthy sugar beet (Beta vulgaris) and sea beet (Beta maritima) were evaluated for their effects on the virulence traits of Bacillus pumilus Isf19, the causal agent of harvested sugar beet root rot disease. The gas chromatographymass spectrometry (GC-MS) analysis revealed that B86, Dez632, Bt851, and Sh622 produced 15, 28, 30, and 20 VOCs, respectively, with high quality. All antagonistic endophytic bacteria produced VOCs that significantly reduced soft root symptoms and inhibited the growth of B. pumilus Isf19 at different levels. The VOCs produced by endophytic bacteria significantly reduced swarming, swimming, and twitching motility by B. pumilus Isf19, which are important to pathogenicity. Our results revealed that VOCs produced by Sh622 and Bt851 significantly reduced attachment of B. pumilus Isf19 cells to sugar beetroots, and also all endophytic bacteria tested significantly reduced chemotaxis motility of the pathogen toward root extract. The VOCs produced by Dez632 and Bt851 significantly upregulated the expression levels of defense genes related to soft rot resistance. Induction of PR1 and NBS-LRR2 genes in sugar beetroot slices suggests the involvement of SA and JA pathways, respectively, in the induction of resistance against pathogen attack. Based on our results, the antibacterial VOCs produced by endophytic bacteria investigated in this study can reduce soft rot incidence.